Interplay of Speech and Meaning in Digital Da’wah: A Speech Act Analysis of Adi Hidayat’s Sermon on Knowledge - Faruq Alhasbi; Faticha Farach Adila; Muhammad Hammam Alizky (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2026)
This study investigates the interplay of speech and meaning in digital da’wah through a speech-act analysis of Adi Hidayat’s sermon “The Importance of Knowledge in Life.” The research is grounded in the understanding that language in a sermon is not merely an information-delivery medium but also a performative act that constructs deeper meanings and persuasive power. A qualitative descriptive method was employed on textual analysis of the sermon transcript using J. L. Austin’s speech act theory, which encompasses locutionary, illocutionary, and perlocutionary acts. The findings reveal that the sermon contains three main types of speech acts: informative (locutionary acts) elements that explain religious concepts, directive (illocutionary acts) elements that provide guidance and exhortations to the audience, and persuasive (perlocutionary acts) elements that generate motivational effects leading to personal transformation. These acts are not presented in isolation but are strategically combined to create a symmetrical relationship between speech and meaning. Such a strategic combination enhances the effectiveness of digital da’wah by integrating cognitive, affective, and conative dimensions of communication. In conclusion, this study affirms that speech act theory is a relevant framework for understanding digital da’wah as a performative communicative practice that not only transfers knowledge but also directs behaviour and fosters religious engagement among contemporary audiences.